PENGARUH GAYA KEPEMIMPINAN VISIONER DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN YANG DIMODERASI OLEH INOVASI DAN KOMPETENSI DIGITAL - Karyono, Karyono; Wahyu Wiryawan, Tri; Suryadi, Suryadi; Hoeroni, Rizqon; Heri Kusumah, Dadang (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study aims to examine the effect of visionary leadership style and organizational culture on employee performance, as well as to analyze the moderating role of innovation and digital competence within organizational settings in Indonesia. The research is motivated by the growing need to enhance employee performance amid organizational dynamics and digital transformation. This study employs a quantitative explanatory approach with a cross-sectional design. Data were collected using a structured questionnaire with a five-point Likert scale from 150 employees in public and private organizations across Indonesia. Data analysis included descriptive statistics, data quality testing, inferential and moderation analysis, and cause–effect mapping using the Fishbone (Ishikawa) Diagram. The results indicate that visionary leadership and organizational culture have a positive and significant impact on employee performance. Furthermore, innovation and digital competence significantly strengthen these relationships as moderating variables. The Fishbone Diagram structure confirms that employee performance is influenced by an integrated set of managerial, human resource, process, and technological factors. These findings highlight the importance of aligning leadership, organizational culture, and digital capability development to achieve sustainable improvements in employee performance.